2022
DOI: 10.3390/ijms23042169
|View full text |Cite
|
Sign up to set email alerts
|

Micro-RNA and Proteomic Profiles of Plasma-Derived Exosomes from Irradiated Mice Reveal Molecular Changes Preventing Apoptosis in Neonatal Cerebellum

Abstract: Cell communication via exosomes is capable of influencing cell fate in stress situations such as exposure to ionizing radiation. In vitro and in vivo studies have shown that exosomes might play a role in out-of-target radiation effects by carrying molecular signaling mediators of radiation damage, as well as opposite protective functions resulting in resistance to radiotherapy. However, a global understanding of exosomes and their radiation-induced regulation, especially within the context of an intact mammali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 100 publications
0
7
0
Order By: Relevance
“…Concerning miR-99b-3p, mesenchymal stem cell-derived EVs (MSC-EVs) promote autophagy of microglial cells through the transfer of miR-99b-3p, thereby relieving neuropathic pain [56]. It may also have an anti-apoptotic/anti-cell death effect in radiation-induced or intraperitoneal disease [57,58]. Regarding miR-422a, plasma exosomal miR-422a serves as the optimal diagnostic biomarker for ischemic stroke [59].…”
Section: Discussionmentioning
confidence: 99%
“…Concerning miR-99b-3p, mesenchymal stem cell-derived EVs (MSC-EVs) promote autophagy of microglial cells through the transfer of miR-99b-3p, thereby relieving neuropathic pain [56]. It may also have an anti-apoptotic/anti-cell death effect in radiation-induced or intraperitoneal disease [57,58]. Regarding miR-422a, plasma exosomal miR-422a serves as the optimal diagnostic biomarker for ischemic stroke [59].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in another recent manuscript [ 51 ], we performed an NGS-based miRNome analysis of plasma exosomes from mice irradiated using the same experimental conditions and with the same radiation doses reported here (SI, PBI and WBI) 24 h post-irradiation. Compared with SI mice, we found 57 significantly differentially expressed miRNAs in plasma exosomes from WBI mice, 13 from PBI mice and only 5 in common between the two different irradiation conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro and in vivo studies have shown that exosomes may play a role in off-target radiation effects by carrying molecular signaling mediators of radiation damage, as well as performing protective functions that lead to resistance to radiation therapy. Moreover, miRNA expression is affected by tissue exposure to radiation, and exosomes from the plasma of irradiated mice prevent radiation-induced apoptosis [19]. Thus, the main factor that transmits information is the quantitative and qualitative miRNA composition of exosomes.…”
Section: Discussionmentioning
confidence: 99%